2017
DOI: 10.1038/srep45358
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxygen and Hydrogen in Crystal Orientation Transition of Copper Foils for High-Quality Graphene Growth

Abstract: The high-quality graphene film can be grown on single-crystal Cu substrate by seamlessly stitching the aligned graphene domains. The roles of O2 and H2 have been intensively studied in the graphene growth kinetics, including lowering the nucleation sites and tailoring the domain structures. However, how the O2 and H2 influence Cu orientations during recrystallization prior to growing graphene, still remains unclear. Here we report that the oxidation of Cu surface tends to stabilize the Cu(001) orientation whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 59 publications
1
28
1
Order By: Relevance
“…19 Herein, we demonstrated a new pathway for the growth of scalable monolayer single-crystalline graphene by seamlessly stitching the unidirectionally aligned arrays of millimeter-sized hexagonal domains using different types of commercially available Cu foils and industrially safe atmospheric pressure conditions. Compared with that reported in similar previous studies, [13][14][15][16][17][18][19] the average size for the hexagonal graphene domains is enlarged by 1-2 orders of magnitude (from tens of micrometers to millimeter); this further eliminates the formation of domain boundaries. The key factor that leads to the success of this growth is the monocrystallization of the catalytic Cu surface to centimeter-sized (111) textures by simply preintroducing a Cu oxide layer for high-temperature surface reconstruction.…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…19 Herein, we demonstrated a new pathway for the growth of scalable monolayer single-crystalline graphene by seamlessly stitching the unidirectionally aligned arrays of millimeter-sized hexagonal domains using different types of commercially available Cu foils and industrially safe atmospheric pressure conditions. Compared with that reported in similar previous studies, [13][14][15][16][17][18][19] the average size for the hexagonal graphene domains is enlarged by 1-2 orders of magnitude (from tens of micrometers to millimeter); this further eliminates the formation of domain boundaries. The key factor that leads to the success of this growth is the monocrystallization of the catalytic Cu surface to centimeter-sized (111) textures by simply preintroducing a Cu oxide layer for high-temperature surface reconstruction.…”
Section: Introductioncontrasting
confidence: 54%
“…However, the attempts based on this approach are oen frustrated by the complication and cost of the Cu surface treatments such as tenuous polishing and/or elongated annealing, tightly rolled Cu foils into a cylinder, etc. [13][14][15][16][17][18] In a recent study reported by Xu et al, the epitaxial growth of meter-sized single-crystal graphene was realized, but a relatively complex experimental setup with small constituent domain sizes (<100 mm) was used, making the probability of the coalesced domain boundaries not negligible even with a 99% unidirectional orientation. 19 Herein, we demonstrated a new pathway for the growth of scalable monolayer single-crystalline graphene by seamlessly stitching the unidirectionally aligned arrays of millimeter-sized hexagonal domains using different types of commercially available Cu foils and industrially safe atmospheric pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] The D peak dispersion at the edge is ∼50 cm -1 / eV, similar to the D peak inside graphite. 41,[58][59][60] That of the 2D and 2D′ peaks is ∼95 and ∼21 cm -1 /eV, respectively, as in refs 17 and 61. Figure 8A plots the spectra for different incident polarization.…”
Section: Band Raman Spectroscopy Of Edgessupporting
confidence: 67%
“…Scanning electron microscopy [39,41] was also employed to characterize crystallographic orientation of graphene. Orientation can be characterized from graphene outlines.…”
Section: Comparison With Other Techniquesmentioning
confidence: 99%
See 1 more Smart Citation